Web-based development for serious game in education - Tan, Zarn Yao (Nanyang Technological University, 2022)
Data structures and algorithms are arguably the most important topic in computer science. Students who aspire to become a software engineer must master this topic as they will be tested on their understanding in this concept thoroughly in every technical interview. However, it can be a tedious process for beginners to pick up this topic as the concepts are mostly abstract. Students might find themselves feeling discouraged and giving up very soon if the learning process is dull.